Yes. Because both equals 1 whole.
Answer:
Second factor is (x - 2).
Step-by-step explanation:
The given polynomial is 3x² -10x + 8 has a factor (3x - 4) and we have to find the other factor.
Now we will factorize the given polynomial to get the other factor.
3x² - 10x + 8
[ Here 8×3 = 24( multiplication of constant term 8 and coefficient of highest degree term) and 6 + 4 = 10 ]
= 3x² - 6x - 4x + 8
= 3x(x - 2) - 4(x - 2)
= (3x -4)(x -2)
In this factorized form we get two factors as (3x -4) and (x -2).
Therefore the second factor is (x - 2).
Answer:
Average rate of change ![=\frac{1}{8}](https://tex.z-dn.net/?f=%3D%5Cfrac%7B1%7D%7B8%7D)
Step-by-step explanation:
Given interval are from ![x=0\ to\ x=5](https://tex.z-dn.net/?f=x%3D0%5C%20to%5C%20x%3D5)
Also,![=\frac{1}{2^3}x=\frac{1}{8}x](https://tex.z-dn.net/?f=%3D%5Cfrac%7B1%7D%7B2%5E3%7Dx%3D%5Cfrac%7B1%7D%7B8%7Dx)
Average rate of change![=\frac{f(b)-f(a)}{b-a}\ for\ given\ interval\ [a,b]](https://tex.z-dn.net/?f=%3D%5Cfrac%7Bf%28b%29-f%28a%29%7D%7Bb-a%7D%5C%20for%5C%20given%5C%20interval%5C%20%5Ba%2Cb%5D)
Here given intervals are ![a=0\ and\ b=5](https://tex.z-dn.net/?f=a%3D0%5C%20and%5C%20b%3D5)
Plugging these value in formula, we get.
Average rate of change![=\frac{\frac{1}{8}(5)-\frac{1}{8}(0)}{5-0}\\\\=\frac{\frac{1}{8}(5)-0}{5-0}\\ \\=\frac{\frac{1}{8}(5)}{5}\\\\=\frac{1}{8}](https://tex.z-dn.net/?f=%3D%5Cfrac%7B%5Cfrac%7B1%7D%7B8%7D%285%29-%5Cfrac%7B1%7D%7B8%7D%280%29%7D%7B5-0%7D%5C%5C%5C%5C%3D%5Cfrac%7B%5Cfrac%7B1%7D%7B8%7D%285%29-0%7D%7B5-0%7D%5C%5C%20%5C%5C%3D%5Cfrac%7B%5Cfrac%7B1%7D%7B8%7D%285%29%7D%7B5%7D%5C%5C%5C%5C%3D%5Cfrac%7B1%7D%7B8%7D)